2020
DOI: 10.1364/ol.413755
|View full text |Cite
|
Sign up to set email alerts
|

161  W middle infrared ZnGeP2 MOPA system pumped by 300  W-class Ho:YAG MOPA system

Abstract: We demonstrated a high-power Q -switched two-stage Ho:YAG master-oscillator power-amplifier (MOPA) system dual-end pumped by Tm:YLF lasers. A new method was introduced by rotating and swapping spatial axial directions of pump beams to improve the beam quality of the Ho:YAG oscillator and first-stage amplifier. Two parallel second-stage Ho:YAG amplifiers were employed to output high power. A total maximum average output power of 332 W at 2091 nm with pulse repetition frequency of 20 kHz was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 65 publications
(22 citation statements)
references
References 11 publications
0
22
0
Order By: Relevance
“…In the past several years, bulk heterojunction polymer solar cells (PSCs) have made much progress due to the developing of nonfullerene small molecule acceptors (NFAs), [ 1–5 ] the power conversion efficiencies (PCEs) have exceeded 17% in the state‐of‐the‐art single‐junction PSCs. [ 6,7 ] Comparing with fullerene acceptors, NFAs have some great advantages, such as a strong absorption among near‐infrared (NIR) range, easy tunability of absorption spectra, and electronic energy levels.…”
Section: Host Binary System the Third Component Voc [V] Jsc [Ma Cm−2]mentioning
confidence: 99%
“…In the past several years, bulk heterojunction polymer solar cells (PSCs) have made much progress due to the developing of nonfullerene small molecule acceptors (NFAs), [ 1–5 ] the power conversion efficiencies (PCEs) have exceeded 17% in the state‐of‐the‐art single‐junction PSCs. [ 6,7 ] Comparing with fullerene acceptors, NFAs have some great advantages, such as a strong absorption among near‐infrared (NIR) range, easy tunability of absorption spectra, and electronic energy levels.…”
Section: Host Binary System the Third Component Voc [V] Jsc [Ma Cm−2]mentioning
confidence: 99%
“…In 2020, Liu et al using a 332 W, 28.9 ns, 20 kHz Ho:YAG laser to pump a mid-infrared ZGP MOPA system. A maximum average power of 161 W was achieved, with the pulse width of 23.3 ns [12]. In the same year, Liu et al reported a 9.8 μm ZGP OPO pumped by a 10 kHz Ho:YAG laser [19].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, nonlinear crystals suitable for producing high power mid and long-wave infrared laser mainly include MgO:PPLN [4], [5], CdSe [6]- [8], BaGa 4 Se 7 (BGSe) [9], [10], OP-GaAs [11], ZnGeP 2 (ZGP), and so on. Among various kinds of nonlinear optical materials, ZGP achieved the highest power of mid and long-wave infrared laser [12], [13], due to its high nonlinear coefficient (d 14 = 75 pm/V), high thermal conductivity, and acceptable damage threshold [14]. Limited by the transmittance range, ZGP needs to be pumped at a wavelength >2 μm.…”
Section: Introductionmentioning
confidence: 99%
“…-SWITCHED Holmium (Ho) lasers are attractive in a variety of applications, such as lidar, surgeries and material processing [1]- [3], which are also the ideal pump sources for non-linear frequency conversion toward 3~14 μm via supercontinuum generation [4] and optical parameter oscillation [5]. Due to the lack of absorption band at 800 nm, Q-switched Ho lasers are mainly pumped by the Thulium (Tm) lasers and 1.9 μm diode lasers (LDs) [6], [7], especially in a MOPA structure with several well-developed high-power Tm lasers [8]. As additional layout for the Tm laser should be prepared for cascade pumping, compactness and accessibility of the pulsed Ho laser are limited [9].…”
Section: Introductionmentioning
confidence: 99%